Do Muslims have equal right to free speech? - Hasan, Md. Mahmudul (OnIslam.net, 2015)
The right to free speech is perhaps a suspect virtue. In other words, writers and commentators may have the right to say what they want and artists, to express what they think or feel curious about. But they are morally obligated to maintain some degree of checks and self-censorship, and consider the socio-religious values and conventional morality that people cherish in a given cultural setting. A book or an artistic piece that insults people’s long-held views, beliefs, convictions and cultural practices and thus can potentially incite violent street demonstrations and can cause death/s is perhaps better not to be produced at all. Perhaps, the debate, whether or not freedom of expression is absolute, may remain a contentious issue for a long time. However, it is almost certain now that Muslims are currently the primary victims of a conceivable hypocrisy in the free speech discourse. While Muslim societies are maligned for a perceived lack of freedom of expression, Muslims do not have equal right to freedom of expression.